Study of The Spatial Footprint of Street Vendors During the Covid-19 Pandemic - Arfan Nur Akbar; Achmad Hery Fuad (Departement of Architecture, Universitas Islam Indonesia, 2022)
This article examines the use of urban space by street vendors during the Covid-19 pandemic. To suppress the spread of Covid-19, adjustments are made to activities in urban spaces, especially in the economic and social sectors. The purpose of this study is to explore the existence of street vendors in the city's green lane in terms of their benefits, problems, and strategies in dealing with the Covid-19 pandemic. This study uses a qualitative method by looking at the research deductively as well as the application of the theory of the production of space by Lefebvre as well as daily studies to reveal the actual situation. Researchers conducted spatial mapping to describe the pattern of street vendors' activities through four typological aspects such as commodities and facilities, temporal, space, and movement. This article shows that spatial mapping also shows the movement and activity of users in space. Spatial practice between street vendors and the community in public spaces can form a strong social space and there is a need for space management during pandemic. Keywords: Covid-19 Pandemic; Social Interaction; Street Vendors; Urban Space